Distribution of healthcare resources in Peninsular Malaysia : An examination of equity with respect to geography and allocative processes / Gan Saw Chien - Gan, Saw Chien (2020)
On a country’s pathway to Universal Health Coverage, it is important to ensure equitable healthcare provision and financing. There was a lack of evidence in equity of healthcare provision and financing across geographic areas in Peninsular Malaysia. This was despite the evidence that geographic factors directly and indirectly affect population health and healthcare services are mostly delivered at immobile healthcare facilities. In Malaysia’s mixed public-private healthcare system, Ministry of Health Malaysia (MOH) has a geographically comprehensive provision network and the MOH resources are distributed through geographic-bound MOH administrative structures. The private sector, which concentrated on more affluent geographic areas, also plays a significant role in providing healthcare services in Peninsular Malaysia. Hence, this study was set out to assess the geographic healthcare equity across states in Peninsular Malaysia. It was, more specifically, to directly assess if the healthcare provision was provided according to healthcare needs across states in Peninsular Malaysia (i.e. horizontal equity in provision), and indirectly assess if the healthcare financing was pro-poorer states in Peninsular Malaysia (i.e. vertical equity in financing). This study also aimed to identify ways to improve the fairness of the healthcare allocative process and equity of healthcare resources distribution. Using regularly collected death registry and survey data from Department of Statistics and MOH, a novel approach, based on the concepts of Lorenz curve, Gini index, concentration curve and concentration index, were adopted to assess the horizontal and vertical geographic equity across states in Peninsular Malaysia in 1997 and 2012. Qualitative inquiry was also carried out to understand the factors influencing the allocation and to determine the fairness of the allocative processes. MOH decision iv makers from various levels were interviewed. Using the Accountability for Reasonableness framework, a framework of four conditions (i.e. relevance, publicity, revision and regulation) for ensuring fairness of the allocative process, as a benchmark, MOH’s success in the allocative process was evaluated. In general, quantitative analysis found that the distributions of overall financial expenditure for hospital care, number of acute beds for hospital care and financial expenditure of primary care in 1997 and 2012 were in line with the principle of horizontal equity in provision. Also, the distributions of MOH primary care financial resources and hospital acute beds were in line with the principle of vertical geographic equity in financing. Nevertheless, no concentrations of MOH hospital financial expenditure in wealthier sates were found. The qualitative inquiry confirmed that the MOH allocative process was geography-based. The operating budget allocation was historical, incremental and often dictated by previous development budget allocation across geographic areas. Evaluation of MOH’s allocative process yielded recommendations such as improving dissemination of decisions and justifications and setting explicit regulations on the allocative process. The findings demonstrated that the geographic equity in Peninsular Malaysia can be further enhanced by ensuring more MOH hospital expenditure are spent in poorer states. The recommendations on the allocative process could help MOH to mitigate unjustified external influence asserted upon the decision makers. (487 words) Key Words: Healthcare Resources, Geographic Equity, Fair Allocative Process